(untitled) - Šusteková, Daniela (Doprava a spoje, 2009)
In this article there are described the using possibilities of GPRS and GPS technologies in the road transport. There is described a concrete realization of this utilization with the functions description using the mobile nets as well as the benefits of this realization.